Phylogenomic analyses and distribution of terpene synthases among Streptomyces - Martín-Sánchez, Lara; Singh, Kumar Saurabh; Avalos, Mariana; van Wezel, Gilles P.; Dickschat, Jeroen S.; Garbeva, Paolina (Beilstein Journal of Organic Chemistry, 2019)
Terpene synthases are widely distributed among microorganisms and have been mainly studied in members of the genus Streptomyces. However, little is known about the distribution and evolution of the genes for terpene synthases. Here, we performed whole-genome based phylogenetic analysis of Streptomyces species, and compared the distribution of terpene synthase genes among them. Overall, our study revealed that ten major types of terpene synthases are present within the genus Streptomyces, namely those for geosmin, 2-methylisoborneol, epi-isozizaene, 7-epi-α-eudesmol, epi-cubenol, caryolan-1-ol, cyclooctat-9-en-7-ol, isoafricanol, pentalenene and α-amorphene. The Streptomyces species divide in three phylogenetic groups based on their whole genomes for which the distribution of the ten terpene synthases was analysed. Geosmin synthases were the most widely distributed and were found to be evolutionary positively selected. Other terpene synthases were found to be specific for one of the three clades or a subclade within the genus Streptomyces. A phylogenetic analysis of the most widely distributed classes of Streptomyces terpene synthases in comparison to the phylogenomic analysis of this genus is discussed.
Keywords: biosynthesis; evolution; geosmin; Streptomyces; terpenes

(untitled) - Barka, E. A.; Vatsa, P.; Sanchez, L.; Gaveau-Vaillant, N.; Jacquard, C.; Klenk, H.-P.; Clément, C.; Ouhdouch, Y.; van Wezel, G. P. (Microbiol. Mol. Biol. Rev., 2016)

(untitled) - Bentley, S. D.; Chater, K. F.; Cerdeño-Tárraga, A.-M.; Challis, G. L.; Thomson, N. R.; James, K. D.; Harris, D. E.; Quail, M. A.; Kieser, H.; Harper, D.; Bateman, A.; Brown, S.; et al. (Nature, 2002)

(untitled) - Bérdy, J. (J. Antibiot., 2005)

(untitled) - Nett, M.; Ikeda, H.; Moore, B. S. (Nat. Prod. Rep., 2009)

(untitled) - Medema, M. H.; Kottmann, R.; Yilmaz, P.; Cummings, M.; Biggins, J. B.; Blin, K.; de Bruijn, I.; Chooi, Y. H.; Claesen, J.; Coates, R. C.; Cruz-Morales, P.; Duddela, S.; et al. (Nat. Chem. Biol., 2015)

(untitled) - Chen, X.; Köllner, T. G.; Jia, Q.; Norris, A.; Santhanam, B.; Rabe, P.; Dickschat, J. S.; Shaulsky, G.; Gershenzon, J.; Chen, F. (Proc. Natl. Acad. Sci. U. S. A., 2016)

(untitled) - Song, C.; Mazzola, M.; Cheng, X.; Oetjen, J.; Alexandrov, T.; Dorrestein, P.; Watrous, J.; van der Voort, M.; Raaijmakers, J. M. (Sci. Rep., 2015)

Natural Product Biosynthesis by Microorganisms and Plant, Part A - Yamada, Y.; Cane, D. E.; Ikeda, H. (Diversity and Analysis of Bacterial Terpene Synthases, 2012)

(untitled) - Yamada, Y.; Kuzuyama, T.; Komatsu, M.; Shin-ya, K.; Omura, S.; Cane, D. E.; Ikeda, H. (Proc. Natl. Acad. Sci. U. S. A., 2015)

(untitled) - Takamatsu, S.; Lin, X.; Nara, A.; Komatsu, M.; Cane, D. E.; Ikeda, H. (Microb. Biotechnol., 2011)

Biotechnology of Isoprenoids - Tholl, D. (Biosynthesis and Biological Functions of Terpenoids in Plants, 2015)

(untitled) - Schulz-Bohm, K.; Martín-Sánchez, L.; Garbeva, P. (Front. Microbiol., 2017)

(untitled) - Dickschat, J. S. (Nat. Prod. Rep., 2016)

(untitled) - Gerber, N. N.; Lechevalier, H. A. (Appl. Microbiol., 1965)

(untitled) - Medsker, L. L.; Jenkins, D.; Thomas, J. F.; Koch, C. (Environ. Sci. Technol., 1969)

(untitled) - McDonald, B. R.; Currie, C. R. (mBio, 2017)

(untitled) - Qin, S.; Feng, W.-W.; Wang, T.-T.; Ding, P.; Xing, K.; Jiang, J.-H. (Plant Soil, 2017)

(untitled) - Jiang, J.; He, X.; Cane, D. E. (Nat. Chem. Biol., 2007)

(untitled) - Baer, P.; Rabe, P.; Fischer, K.; Citron, C. A.; Klapschinski, T. A.; Groll, M.; Dickschat, J. S. (Angew. Chem., Int. Ed., 2014)

(untitled) - Christianson, D. W. (Chem. Rev., 2017)

(untitled) - Seemann, M.; Zhai, G.; de Kraker, J.-W.; Paschall, C. M.; Christianson, D. W.; Cane, D. E. (J. Am. Chem. Soc., 2002)

(untitled) - Dickschat, J. S.; Bode, H. B.; Mahmud, T.; Müller, R.; Schulz, S. (J. Org. Chem., 2005)

(untitled) - Jiang, J.; Cane, D. E. (J. Am. Chem. Soc., 2008)

(untitled) - Nawrath, T.; Dickschat, J. S.; Müller, R.; Jiang, J.; Cane, D. E.; Schulz, S. (J. Am. Chem. Soc., 2008)

(untitled) - Dickschat, J. S.; Nawrath, T.; Thiel, V.; Kunze, B.; Müller, R.; Schulz, S. (Angew. Chem., Int. Ed., 2007)

(untitled) - Wang, C.-M.; Cane, D. E. (J. Am. Chem. Soc., 2008)

(untitled) - Komatsu, M.; Tsuda, M.; Omura, S.; Oikawa, H.; Ikeda, H. (Proc. Natl. Acad. Sci. U. S. A., 2008)

(untitled) - Köksal, M.; Chou, W. K. W.; Cane, D. E.; Christianson, D. W. (Biochemistry, 2012)

(untitled) - Zhao, B.; Lin, X.; Lei, L.; Lamb, D. C.; Kelly, S. L.; Waterman, M. R.; Cane, D. E. (J. Biol. Chem., 2008)

(untitled) - Lin, X.; Hopson, R.; Cane, D. E. (J. Am. Chem. Soc., 2006)

(untitled) - Rabe, P.; Dickschat, J. S. (Angew. Chem., Int. Ed., 2013)

(untitled) - Rabe, P.; Schmitz, T.; Dickschat, J. S. (Beilstein J. Org. Chem., 2016)

(untitled) - Citron, C. A.; Gleitzmann, J.; Laurenzano, G.; Pukall, R.; Dickschat, J. S. (ChemBioChem, 2012)

(untitled) - Citron, C. A.; Barra, L.; Wink, J.; Dickschat, J. S. (Org. Biomol. Chem., 2015)

(untitled) - Nakano, C.; Horinouchi, S.; Ohnishi, Y. (J. Biol. Chem., 2011)

(untitled) - Nakano, C.; Tezuka, T.; Horinouchi, S.; Ohnishi, Y. (J. Antibiot., 2012)

(untitled) - Cane, D. E.; Tandon, M. (Tetrahedron Lett., 1994)

(untitled) - Cane, D. E.; Tandon, M. (J. Am. Chem. Soc., 1995)

(untitled) - Cane, D. E.; Tandon, M.; Prabhakaran, P. C. (J. Am. Chem. Soc., 1993)

(untitled) - Kim, S.-Y.; Zhao, P.; Igarashi, M.; Sawa, R.; Tomita, T.; Nishiyama, M.; Kuzuyama, T. (Chem. Biol., 2009)

(untitled) - Janke, R.; Görner, C.; Hirte, M.; Brück, T.; Loll, B. (Acta Crystallogr., Sect. D: Biol. Crystallogr., 2014)

(untitled) - Riclea, R.; Citron, C. A.; Rinkel, J.; Dickschat, J. S. (Chem. Commun., 2014)

(untitled) - Rabe, P.; Samborskyy, M.; Leadlay, P. F.; Dickschat, J. S. (Org. Biomol. Chem., 2017)

(untitled) - Aoyagi, T.; Aoyama, T.; Kojima, F.; Hattori, S.; Honma, Y.; Hamada, M.; Takeuchi, T. (J. Antibiot., 1992)

(untitled) - Cane, D. E.; Abell, C.; Tillman, A. M. (Bioorg. Chem., 1984)

(untitled) - Cane, D. E.; Tillman, A. M. (J. Am. Chem. Soc., 1983)

(untitled) - Lesburg, C. A.; Zhai, G.; Cane, D. E.; Christianson, D. W. (Science, 1997)

(untitled) - Cane, D. E.; Oliver, J. S.; Harrison, P. H. M.; Abell, C.; Hubbard, B. R.; Kane, C. T.; Lattman, R. (J. Am. Chem. Soc., 1990)

(untitled) - Cane, D. E.; Sohng, J.-K.; Lamberson, C. R.; Rudnicki, S. M.; Wu, Z.; Lloyd, M. D.; Oliver, J. S.; Hubbard, B. R. (Biochemistry, 1994)

(untitled) - Gutta, P.; Tantillo, D. J. (J. Am. Chem. Soc., 2006)

(untitled) - Zu, L.; Xu, M.; Lodewyk, M. W.; Cane, D. E.; Peters, R. J.; Tantillo, D. J. (J. Am. Chem. Soc., 2012)

(untitled) - Darby, C. A.; Stolzer, M.; Ropp, P. J.; Barker, D.; Durand, D. (Bioinformatics, 2017)

(untitled) - Emms, D. M.; Kelly, S. (Genome Biol., 2015)

(untitled) - Emms, D. M.; Kelly, S. (Mol. Biol. Evol., 2017)

(untitled) - Katoh, K.; Standley, D. M. (Mol. Biol. Evol., 2013)

(untitled) - Criscuolo, A.; Gribaldo, S. (BMC Evol. Biol., 2010)

(untitled) - Darriba, D.; Taboada, G. L.; Doallo, R.; Posada, D. (Bioinformatics, 2011)

(untitled) - Stamatakis, A. (Bioinformatics, 2014)

(untitled) - Kearse, M.; Moir, R.; Wilson, A.; Stones-Havas, S.; Cheung, M.; Sturrock, S.; Buxton, S.; Cooper, A.; Markowitz, S.; Duran, C.; Thierer, T.; Ashton, B.; et al. (Bioinformatics, 2012)

(untitled) - Sydykova, D. K.; Jack, B. R.; Spielman, S. J.; Wilke, C. O. (F1000Research, 2018)

(untitled) - Pond, S. L. K.; Frost, S. D. W.; Muse, S. V. (Bioinformatics, 2005)

(untitled) - Smith, M. D.; Wertheim, J. O.; Weaver, S.; Murrell, B.; Scheffler, K.; Kosakovsky Pond, S. L. (Mol. Biol. Evol., 2015)

(untitled) - Murrell, B.; Moola, S.; Mabona, A.; Weighill, T.; Sheward, D.; Kosakovsky Pond, S. L.; Scheffler, K. (Mol. Biol. Evol., 2013)

(untitled) - Bansal, M. S.; Wu, Y.-C.; Alm, E. J.; Kellis, M. (Bioinformatics, 2015)